The acceptability of Prolonged Exposure Therapy for Primary Care (PE-PC) for the treatment of PTSD in a low resourced community in the Eastern Cape - Leboho, Lerato (Rhodes University, Faculty of Humanities, Department of Psychology)
Post-traumatic stress disorder (PTSD) is a global mental health concern, especially in low- resourced communities that are characterised by limited access to health professionals, limited healthcare infrastructure, and limited access to evidence-based mental healthcare at primary care level. Over the last decade, several psychological trauma-focused therapies (TFTs), such as prolonged exposure therapy (PE) have been developed to treat PTSD. In the context of the existing literature, studies done in HICs have explored the implementation and acceptability of prolonged exposure therapy at primary care level (PE-PC) as a first-line treatment for PTSD. Contrary to this, there is little to no implementation studies done to date that have examined the acceptability of empirically supported treatments (ESTs), such as PE in low-resourced countries, such as South Africa. Using the Implementation Science framework, ten participants were recruited to be interviewed, using semi-structured interviews, about their experiences and perceptions of PE-PC as a treatment for PTSD, and to also share their experiences of living with PTSD. The interview data was analysed using the reflexive thematic analysis (RTA) method to determine whether PE-PC is an acceptable treatment for PTSD that can be administered at community level and highlights the importance of integrating mental health within primary healthcare practice. Based on the analysis four superordinate themes were identified, namely, lack and absence of social support; factors preventing trauma survivors from accessing EBTs; lack of knowledge regarding mental health literacy, and adaptation of a brief trauma-focused therapy in a low-resource community. The evidence this study shows that some of the factors that hinder the acceptability of trauma-focused therapies (TFTs) at community level, include stigma and discrimination, the absence of social support, limited resources, and inadequate knowledge on mental health and illness. Therefore, it makes sense of the urgency to implement evidence-based treatments (EBTs) in LMICs. Findings of this thesis suggest that (a) PE-PC should be adopted at community level, and that (b) PE-PC is an acceptable treatment for PTSD in low-resourced communities.
Keywords: Post-traumatic stress disorder; Prolonged exposure therapy; Primary care (Medicine) -- South Africa -- Eastern Cape; Trauma therapy; Poor Medical care -- South Africa -- Eastern Cape